Navigation System of an Unmanned Boat for Autonomous Analyses of Water Quality - Tuna, G.; Arkoc, O.; Koulouras, G.; Potirakis, S. M. (Elektronika ir Elektrotechnika, 2013)
This paper presents a navigation system for autonomous analyses of water quality using unmanned boats at drinking water reservoirs such as dams and holding ponds. As it is well-known, water quality plays an important role in controlling health and the state of disease. Therefore, it needs to be analyzed at periodical intervals. Various systems exist for automatic analyses of water quality and the common problem of these systems is the complexity associated with collecting samples. To deal with this problem, an autonomous boat loaded with a Sonde with probes can be used for analyzing the quality of water. In this study, the navigation system of the autonomous boat is investigated in detail. In order to prove the effectiveness of the proposed system, MATLAB-based simulation studies were conducted. The results of these simulation studies show that the proposed system can navigate an unmanned boat successfully at drinking water reservoirs. Field tests with an autonomous boat are in progress. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5387